Improving Teacher’s Performance Through Academic Supervision and Principal’s Interpersonal Competence - Nursanty, Devy (PPSDP International Journal of Education, 2022)
The goal of this study was to look at the use of academic supervision and how it relates to the principal's interpersonal competency in boosting teacher’s performance. A qualitative analytical strategy was applied in this investigation. Sources of information for this study were gathered through the use of interview, observation, and documentation approaches. The gathered data were then aggregated, selected based on quality, and descriptively evaluated, with the results concluding to solve the existing difficulties. The findings of this study suggest that combining academic supervision from the principal with effective interpersonal communication might increase teacher’s performance. And there is feedback via excellent communication in overcoming challenges experienced by instructors compassionately by partnering to integrate perspectives and mental processes with the goal of enhancing education through the interpersonal method.